Information technology - Metadata registries (MDR) Part 3: Registry metamodel and basic attributes : Amendment 1 = Technologies de l'information Registres de métadonnées (RM) Partie 3: Métamodèle de registre et attributs de base : Amendment 1 (ISO/IEC, 2020)
The procedures used to develop this document and those intended for its further maintenance are described in the ISO/IEC Directives, Part 1. In particular, the different approval criteria needed for the different types of document should be noted. This document was drafted in accordance with the editorial rules of the ISO/IEC Directives